Funções ecossistêmicas e redundância funcional de vertebrados marinhos recifais do Oceano Atlântico - Severo, Luiza Waechter (2020)
The role played by species at the local scale, known as ecological function, ensures ecosystem functioning and the provision of ecosystem services. The overlap ecosystem functions between different species characterizes functional redundancy, an insurance against local extinctions and population declines. Under conditions of low functional redundancy, the ecosystem becomes more vulnerable to biodiversity losses. In Atlantic Ocean reefs, vertebrates such as sea turtles, mammals and fish (Elasmobranchii and Teleostei) are important fauna components and their functions range from the construction of reef structure to trophic regulation. However, there are gaps in the understanding of ecosystem functions and the degree of functional redundancy between these groups. In this context, our project aims to (i) compile and categorize the ecosystem functions of 224 marine reefs species in the Atlantic Ocean, (ii) identify the degree of functional redundancy between species in these four taxonomic groups, (iii) assess species richness and functional originality patterns at the local scale, and (iv) investigate functional loss following the removal of threatened species in Atlantic Ocean reefs. We compiled six functional traits related to the performance of species in ecosystem functions and calculated functional diversity (FRic), functional originality (FUn), functional redundancy (FRed). Further, we estimated the effects of species’ loss over functional diversity in reefs. Our results reveal seven ecosystem functions performed by vertebrates in Atlantic reefs. Furthermore, 44.8% of the functional volume is filled by threatened species and “Top predators” have the highest proportion of threatened species (53.8%; n=21). At the regional scale, different taxonomic groups overlap in functional space (mainly between Elasmobranchii and Teleostei), an evidence that considering this set of traits vertebrates of distinct lineages may still be redundant. Regional functional redundancy also holds at the local scale. The Caribbean, a biodiversity hotspot in the Atlantic, showed greater taxonomic and functional richness patterns (n=134; 77.9% of regional functional volume).The removal of mesopredator species had the greatest effect on losses in the functional space, where the removal of 50% of the species will cause approximately 60% of functional loss on the Brazilian coast, for example.